Influência de Ajustes de Imagem na Distorção de Implantes e na Mensuração Tomográfica da Espessura Óssea Vestibular a Implantes Dentário - Mello, Hugo Nogueira (2024)
Dental implants are among the best treatment options for replacing lost teeth, as they restore the aesthetics, function, and self-esteem of patients. Although cone beam computed tomography (CBCT) is the preferred three-dimensional technique for assessing peri-implant vestibular bone, this examination has deficiencies and limitations. When an implant positioned near the vestibular bone wall is evaluated in CBCT images, the thickness of this bone plate is difficult to measure due to artifacts related to the implant, such as Scatter, Blooming, and the Partial Volume Effect. Thus, the dimensional accuracy of some structures may be compromised, affecting the final diagnosis and proposed treatment plan. The objective of this study was to evaluate whether adjustments to filter and contrast can improve the accuracy of CBCT in measuring the vestibular bone plate adjacent to osseointegrated implants by reducing blooming expression. For this purpose, homogeneous bone blocks with implants installed at different distances from the vestibular bone wall (thicknesses of 0.3 mm, 0.5 mm, and 1 mm) were used. Three dentists independently evaluated 234 images, measuring the thickness of the vestibular bone plate and the diameter of the implants, with the 'Sharpen' filter activated and deactivated, and using three different contrast settings. Tomographic measurements were subtracted from the actual measurements, and relative differences were subjected to repeated measures ANOVA with a significance level of 5%. In the group with the smallest thickness (0.3 mm), there was a greater difference between tomographic and actual measurements (79.9% ± 29.0%) than in the 0.5 mm (36.1% ± 38.4%) and 1 mm (29.4% ± 12.3%) groups (p<0.05). For the implant diameter factor, the activation of the 'Sharpen' filter provided tomographic measurements closer to actual measurements than when deactivated (p<0.05). Measurements of the vestibular bone plate and implant diameter were not influenced by contrast adjustment (p>0.05). In conclusion, contrast adjustments did not reduce implant distortion or influence the accuracy of tomographic measurement of the vestibular bone plate. Although filter activation reduced implant distortion associated with blooming, it did not influence the measurement of the vestibular bone plate.